The forever house - Laguna, Sofie 1968- (Puffin, 2012)
Fenella can only dream of having a cat of her own. But then an unwanted stray makes his home in her old cubby, the Forever House
Keywords: Pets / Juvenile fiction; Cats / Juvenile fiction; Children's stories